Obesity and Metabolic Syndrome - Liu, MD, Zhao (North American Journal of Medicine and Science, 2009)
Obesity has become a serious global public health problem. World Health Organization (WHO) estimates that over 1.7 billion people around the world are overweight and 310million are obese.1 Within the US, two sources of data are available on the prevalence of obesity. One is from the Behavioral Risk Factor Surveillance Survey (BRFSS). These data come from self-reported heights and weights, obtained by telephone interviews. Given the tendency of underestimation of one’s weight and overestimation of one’s height, the result is likely an underestimate of the actual prevalence of obesity. Nonetheless, according to the BRFSS data, 25% of the population in most states were obese in 2007, and some exceeding 30%. The National Health and Nutrition Examination Surveys data are obtained by direct measurement of heights and weights. According to the most recent data released in November 2007, over 72million American adults are obese, and this represents 33.3% of men and 35.3% of women of the American adult population.